Psikoedukasi Deromantisasi Gangguan Mental pada Komunitas Online - Cleoputri Yusainy; Dita Rachmayani (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This public service activity aims at increasing literacy on the complexity of mental disorders. We used the form of public education on psychology (‘psych-ed’) focusing on the issue of deromanticization of mental disorders. The activity was conducted in collaboration with Manusiabiasa digital community, involving 111 participants from younger audiences (mean age = 22.48 years old; SD = 5.33; 87.79% females). A self-reported questionnaire was employed to compare participants’ percentages of presenting correct answers before and after the psych-ed. Based on Wilcoxon signed-rank test, we found an overall increase in participants understanding, mainly on subtopics regarding views on diagnoses of mental disorders, the impact of deromanticizing mental disorders, and interventions for mental disorders. Further psych-ed is required on the subtopic of perspectives on mental disorders specifically.